Kageneckia oblonga Leaves Subjected to Different Drying Methods: Drying Kinetics, Energy Consumption and Interesting Compounds - Zambra, Carlos; Hernández, Diógenes; Reyes, Hugo; Riveros, Nicole; Lemus-Mondaca, Roberto (Frontiers in Sustainable Food Systems, 2021)
In this study, Kageneckia oblonga leaves were dried under different drying conditions and techniques (oven drying (NC), vacuum drying (VNC), convective drying (FC) and microwave-assisted convective drying (MWFC)). Thus, the effect of temperature, vacuum and microwave on the drying features of K. oblonga leaves was determined. Fick’s second law was used to calculate the effective moisture diffusivity that varied from 3.94 – 8.14×10-11 m2/s, 1.12 – 1.40×10-11 m2/s, 7.83 – 11.36×10-11 m2/s, and 6.93 – 16.72×10-11 m2/s for NC, VNC, FC and MWFC methods, respectively. In addition, the Weibull and Midilli–Kucuk models accurately predicted all experimental drying curves of K. oblonga leaves. Regarding the energy consumption and efficiency values for different drying methods of K. oblonga were found to be in the range of 0.20 – 7.50 kW·h and 0.10 – 3.70 %, respectively. The results showed that MWFC method does not significantly affect the phenolic compounds and could be used for large-scale production of K. oblonga dried leaves.